Christian Social Teachings : A Reader in Christian Social Ethics from the Bible to the Present - Childs, James M., 1939-; Forell, George W. (George Wolfgang), 1919-2011 (Book collections on Project MUSE., 2013)
Jesus as an instigator of revolutionary change. This classic collection of Christian statements on social ethics, now fully revised and augmented, provides a panoramic view of the 2000-year development of Christian concerns for political justice, peace, civil rights, family law, civil liberties, and other ""worldly"" issues